Learning Media Design for Shorof Lesson to Improve Students' Learning Interest Using a Storyline Articulate Program for Intensive First Grade Students at Darussalam Modern Gontor Islamic Institution for girl Campus 2 - Ahmad Hidayatullah Zarkasyi; Zuhrotul Mufidah; Fairuz Subakir Ahmad (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2021)
Darussalam Modern Gontor Islamic Institution for Girls second campus gives great attention to the teaching of Arabic. And always striving to improve students' Arabic language skills from all aspects, from activities inside and outside the classroom. Like student one intensive in particular, is considered as the initial phase in learning Arabic rules such as nahwu and shorof. So some students, especially in studying shorof, find it difficult and bored, causing a decrease in their interest and learning achievement. From the results of observations and interviews to overcome the problems that occur researchers see the design of instructional media development is needed. The development in question is the use of modern technology. That is, by using the Articulate Storyline application which aims to assist teachers in explaining easily and improving students' learning abilities or achievements This research is a type of Research and Development (R&D) research peneliti where researchers start by conducting interviews and dialogues with Shorof lecturers and students of class one intensive at Modern Islamic Boarding School second campus . In collecting data, researchers used observas, interviews, tests, and questionnaires. Researchers also used several research instruments, such as observation guides, interview guides, test questions, and questionnaire sheets. In data analysis, researchers used the t-test formula. Based on the results of the trial, this study can be concluded that the feasibility of developed learning media products in the form of (1) division of learning material shorof consists of muqoddimah and 5 chapters namely ، muqoddimah, chapter 1 (Shighoh), chapter 2 (al-Fi'il), chapter 3 (Auzan al-Fi'il), chapter 4 (Tashrif al-Af'al al-Lughow, al-madhi, al-mudhori ', al-amr) chapter 5 (al-mazidat fi al-af'al). That is the value of t 0.774 is greater than the value of t test, which is in table 2.021 so that the null hypothesis is rejected, which means the developed media is effective to improve the student's learning ability in learning shorof materi